2015
DOI: 10.1080/15384047.2015.1026478
|View full text |Cite
|
Sign up to set email alerts
|

Arginine deprivation by arginine deiminase ofStreptococcus pyogenescontrols primary glioblastoma growthin vitroandin vivo

Abstract: Arginine auxotrophy constitutes a weak point of several tumors, among them glioblastoma multiforme (GBM). Hence, those tumors are supposed to be sensitive for arginine-depleting substances, such as arginine deiminase (ADI). Here we elucidated the sensitivity of patient-individual GBM cell lines toward Streptococcus pyogenes-derived ADI. To improve therapy, ADI was combined with currently established and pre-clinical cytostatic drugs. Additionally, effectiveness of local ADI therapy was determined in xenopatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 26 publications
(32 reference statements)
4
40
0
1
Order By: Relevance
“…In a previous publication by Syed et al, 22 % of primary GBM cultures were found to harbor a methylated CpG island in the ASL core promoter, leading to significant downregulation of ASL mRNA [27]. In our own studies on patient-derived GBM cell lines, comparable results were obtained, with reduced ASL mRNA levels in half of the examined cases (12 in total) [30]. Additional genes OTC and arginase I were almost entirely downregulated in this cohort, whereas carbamoyl phosphate synthase I was expressed by all cell lines [31].…”
Section: Arginine Auxotrophy In Human Malignanciessupporting
confidence: 75%
See 2 more Smart Citations
“…In a previous publication by Syed et al, 22 % of primary GBM cultures were found to harbor a methylated CpG island in the ASL core promoter, leading to significant downregulation of ASL mRNA [27]. In our own studies on patient-derived GBM cell lines, comparable results were obtained, with reduced ASL mRNA levels in half of the examined cases (12 in total) [30]. Additional genes OTC and arginase I were almost entirely downregulated in this cohort, whereas carbamoyl phosphate synthase I was expressed by all cell lines [31].…”
Section: Arginine Auxotrophy In Human Malignanciessupporting
confidence: 75%
“…3). This is accompanied by cell cycle alterations (G 1 or S phase arrest), as proven for pancreatic and breast cancer as well as GBM cells [30,31,71].…”
Section: Stress Responses Upon Adi-based Therapy -Autophagy Senescenmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of amino acid depletion contributing to antibrain tumor activity may not be unique to Asn and Gln, because others have demonstrated similar anti-GBM effects with manipulation of arginine metabolism (38,39). Our study adds evidence justifying further research on amino acid manipulation for development of brain tumor therapeutics.…”
Section: Discussionmentioning
confidence: 70%
“…Была доказана способ-ность фермента, подавлять пролиферацию моно-нуклеарных лейкоцитов периферической крови, клеток глиобластомы, клеток карциномы кожи А431 и др. [9,13,21]. В то же время действие АД из S. pyogenes в отношении эндотелиальных кле-ток остается недостаточно изученным.…”
Section: Discussionunclassified